Chemistry and metallurgy in New Spain: the work of Xavier Alexo Orrio (18th century) - Aceves, Patricia (Circumscribere International Journal for the History of Science, 2012)
Studies on the origin and development of modern chemistry and metallurgy in Mexico are scarce. The present study analyzes a manuscript from mid-18th century entitled Metalogia o Physica de los metals (Metallogy or Physics of metals), by Jesuit Xavier Alexo Orrio. The first volume of that book discusses systematically theoretical and practical features of the chemistry of metals, thus allowing for a glimpse into various procedures, doctrines, conceptions, and interpretations taken from a multiplicity of different authors including friars, alchemists, and rationalistic, Aristotelian, technical and craftsmen chemists. The book content represents the conjectural nature of theoretical and experimental chemistry, as well the eclecticism of Jesuit teaching at the middle of the 18th century.